Aperture - Computer Architecture Made Visual - Rodrigues, Christofer; Gonçalves, Rogério Aparecido; Fabrício Filho, João (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2025)
Computer Architecture and Organization (CAO) is a recurring curricular component in technology courses. However, the content covered in this subject ends up being limited to abstract concepts about how components work, sometimes aided by the use of diagrams. Thus, we propose the implementation of a material focused on visualization and interactivity with the components studied, allowing the observation of the signals that pass through the circuits, such as in an adder, or the control signals of a processor. The material produced incrementally delivers basic digital logic circuits, such as adders, or memories, and gradually increases in complexity, reaching the implementation of a MIPS processor with a 5-stage pipeline based on the book by David A. Patterson and John LeRoy Hennessy. With this work, we intend to facilitate the process of studying AOC by providing material with a focus on visualization and interactivity that complements traditional forms of teaching.